Sinusoidal Vibration Source Localization in Two-Dimensional Space Around the Hand - Ujitoko, Yusuke; Kuroki, Scinob (Frontiers in Psychology, 2022)
There are use cases where presenting spatial information via the tactile sense is useful (e.g., situations where visual and audio senses are not available). Conventional methods that directly attach a vibrotactile array to a user's body present spatial information such as direction by having users localize the vibration source from among the sources in the array. These methods suffer from problems such as heat generation of the actuator or the installation cost of the actuators in a limited space. A promising method of coping with these problems is to place the vibrotactile array at a distance from the body, instead of directly attaching it to the body, with the aim of presenting spatial information in the same way as the conventional method. The present study investigates the method's effectiveness by means of a psychophysical experiment. Specifically, we presented users with sinusoidal vibrations from remote vibrotactile arrays in the space around the hand and asked them to localize the source of the vibration. We conducted an experiment to investigate the localization ability by using two vibration frequencies (30 Hz as a low frequency and 230 Hz as a high frequency). We chose these two frequencies since they effectively activate two distinctive vibrotactile channels: the rapidly adapting afferent channel and the Pacinian channel. The experimental results showed that humans can recognize the direction of the vibration source, but not the distance, regardless of the source frequency. The accuracy of the direction recognition varied slightly according to the vibration source direction, and also according to the vibration frequency. As expected, the accuracy of direction recognition decreased as the source became farther away, and the degree of decrease was especially large with the low frequency source. These results suggest that it is better to design a spatial information presenting device considering the direction, distance, and frequency of the vibration source.